Implementation of Bali Provincial Regulation No. 5 of 2020 on Balinese Cultural Tourism Standards in Cemagi Village, Badung Regency - Indrayana, Cokorda Putra; Handoko, V. Rudy; Wirata, Gede (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the implementation of Bali Provincial Regulation No. 5 of 2020 concerning the Standards for the Implementation of Balinese Cultural Tourism in Cemagi Tourism Village, Badung Regency, and to identify key challenges that hinder its effective execution. Methodology/approach: The research employs a qualitative case study approach involving in-depth interviews, observations, document analysis, and purposive sampling of stakeholders, including tourism village managers, local guides, educators, and community members. Data were analyzed through condensation, display, and conclusion-drawing techniques to obtain a comprehensive understanding of policy implementation. Results/findings: The findings indicate that although the regulation has been partially implemented, several critical issues persist. Cultural-based accommodation facilities do not fully comply with the standards mandated by the regulation. Coordination among implementing agencies remains weak, and communication between government and local communities is inconsistent. Additional challenges include land-use conversion, insufficient public facilities such as parking areas, and limited human resource capacity, particularly the lack of trained and registered local tour guides. Conclusion: The implementation of the regulation in Cemagi Village has not yet met expectations, primarily due to gaps in cultural accommodation management, inadequate coordination, and resource limitations. Strengthening institutional collaboration, enhancing human resource quality, and improving village infrastructure are essential to achieving the regulation’s objectives. Limitations: This study focuses solely on Cemagi Tourism Village and does not generalize to all tourism villages in Bali. Findings are based on qualitative data and may not capture broader regional variations. Contribution: The study provides empirical insights into policy implementation challenges in cultural-based tourism villages and offers recommendations to support more sustainable and culturally aligned tourism governance in Bali.